2009
DOI: 10.1016/j.jbiomech.2009.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Contact stress distributions on the femoral head of the emu (Dromaius novaehollandiae)

Abstract: Osteonecrosis of the femoral head remains a challenging orthopaedic problem. The disease frequently progresses to femoral head collapse, leading to debilitating osteoarthritis in the affected hip(s). Since a major goal of pre-collapse interventions is to forestall the need for hip arthroplasty, it is important that any animal models used to develop or study such interventions also have a natural history of progression to femoral head collapse. The emu (Dromaius novaehollandiae), a large flightless bird native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…joint. ABAD excursions during maneuvers were extremely small (less than 8 deg across all six trials shown), as expected given interaction between the proximal femur and the pelvic antitrochanter (Hutchinson and Gatesy, 2000;Hertel and Campbell, 2007;Troy et al, 2009). However, contrary to the assertion that the antitrochanter prevents femoral long-axis mobility by acting as a lock (Hertel and Campbell, 2007), we document significant hip LAR in maneuvering guineafowl.…”
Section: A Predominant Role For Larsupporting
confidence: 71%
See 2 more Smart Citations
“…joint. ABAD excursions during maneuvers were extremely small (less than 8 deg across all six trials shown), as expected given interaction between the proximal femur and the pelvic antitrochanter (Hutchinson and Gatesy, 2000;Hertel and Campbell, 2007;Troy et al, 2009). However, contrary to the assertion that the antitrochanter prevents femoral long-axis mobility by acting as a lock (Hertel and Campbell, 2007), we document significant hip LAR in maneuvering guineafowl.…”
Section: A Predominant Role For Larsupporting
confidence: 71%
“…Likewise, analyses of joint rotation are usually restricted to flexion/extension (FE) angles (Sigmund, 1959;Cracraft, 1971;Rylander and Bolen, 1974;Jacobson and Hollyday, 1982;Manion, 1984;Gatesy, 1990;Gatesy, 1999;Johnston and Bekoff, 1992;Abourachid and Renous, 2000;Reilly, 2000;Verstappen et al, 2000;Ellerby and Marsh, 2010;Smith et al, 2010;Nyakatura et al, 2012). Given the relatively small transverse component of the ground reaction force during forward locomotion (Clark and Alexander, 1975;Main and Biewener, 2007;Troy et al, 2009), inverse dynamic studies normally emphasize net FE joint moments as well (Roberts, 2001;Roberts and Scales, 2004;Daley et al, 2007;Rubenson and Marsh, 2009;Andrada et al, 2013b). Our current perception of bird hind limbs thus remains deeply rooted in the erect paradigm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Troy, Brown & Conzemius (2009) assumed that only the IFE, ITM, ITCR and PIFML muscles (homologous to ours) would resist hip adduction in their simplified emu model, but our analysis reveals that several more hip abductors exist, namely the IL, ILFB, FCM/L and CFP muscle groups (Table 4; Figs. 14 and 15).…”
Section: Discussionmentioning
confidence: 86%
“…Hutchinson and Gatesy () noted the antitrochanter's function as a physical limit to femoral abduction during stance and locomotion and is thus likely loaded in both compression and shear. In contrast, Hertel et al () and Troy et al () suggested the antitrochanter functions as a sliding surface against the femoral neck, and experiences little compression during stance and locomotion. Prior to skeletal maturity, the avian antitrochanter attaches to the laterally oriented growth plate surfaces on the ilial‐ischial junction, and is comprised of a hyaline cartilage core and a fibrocartilaginous articular surface.…”
Section: Discussionmentioning
confidence: 99%